"Ceci n'est pas un fragment": Identity, Intertextuality and Fictionality in Sappho's "Brothers Poem". Issue 1 (1st January 2016) - Bär, Silvio
Abstract : In this article, Sappho's Brothers Poem is re-evaluated and analysed from various perspectives that have not been addressed sufficiently in scholarship so far. First, some questions of principle regarding the role of the brothers and the Sapphic speaker are discussed. Secondly, the poem's communicative situation is examined, and different options for the identification of the person addressed as "you" are considered. Thirdly, it is demonstrated how the poem establishes an intertextual dialogue with the Homeric Odyssey on various levels, and how this dialogue affects the general understanding of the poem. Finally, the commonly held view that the five transmitted stanzas do not represent the entire poem is challenged. The article concludes with some wider considerations about some of the most common assumptions regarding the nature and the fragmentary state of the Brothers Poem .